Pengaruh Model Pembelajaran Guided Inquiry Berbantuan E-LKPD terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik pada Materi Sistem Pernapasan di Kelas XI SMA Negeri 17 Samarinda - Margaretha Dhea Kristiani; Sri Purwati; Herliani Herliani; Sonja Verra Tinneke Lumowa; Suparno Putera Makkadafi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the lack of variety of learning models that cause students' critical thinking skills and learning outcomes to be still low. Therefore, the guided inquiry model assisted by E-LKPD is used as an alternative to facilitate the investigation process in a directed manner. This study aims to determine the effect of the guided inquiry learning model assisted by E-LKPD on students' critical thinking skills and learning outcomes in the respiratory system material of grade XI at SMA Negeri 17 Samarinda. This research is a quantitative study with a quasi-experimental type, using a non-equivalent control group design. Data collection techniques used pretest and posttest. The research sample consisted of 25 students per class. The experimental class used the guided inquiry model assisted by E-LKPD, while the control class used the Student Teams Achievement Divisions (STAD) model. The results of the t-test (independent sample t-test) showed sig. (2-tailed) of 0.000 < 0.05 and tcount > ttable, namely 4.448 ˃ 2.010 for critical thinking skills, and 4.903 ˃ 2.010 for student learning outcomes. The results of the study indicate that the guided inquiry learning model assisted by E-LKPD has a significant effect on improving critical thinking skills and student learning outcomes in the respiratory system material.